2016
DOI: 10.1083/jcb.201505082
|View full text |Cite
|
Sign up to set email alerts
|

Mesp1 controls the speed, polarity, and directionality of cardiovascular progenitor migration

Abstract: The transcription factors Mesp1 and Mesp2 are equally efficient at promoting specification, EMT, and differentiation of early multipotent cardiovascular progenitors. However, only Mesp1 promotes the speed, polarity, and directionality of cell migration, explaining how Mesp1 coordinates progenitor fate decision and migration during development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 49 publications
3
53
0
1
Order By: Relevance
“…The heart rudiment develops from a single pair of blastomeres in the 64‐cell stage, together with several other body muscles . The descendants of these blastomeres express Mesp , which has an essential role in the speed of migration and the specification of multipotent cardiac progenitor cells . In ascidians, Mesp1/2 is regulated by beta‐catenin, Tbx6 , and others.…”
Section: Cardiac Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heart rudiment develops from a single pair of blastomeres in the 64‐cell stage, together with several other body muscles . The descendants of these blastomeres express Mesp , which has an essential role in the speed of migration and the specification of multipotent cardiac progenitor cells . In ascidians, Mesp1/2 is regulated by beta‐catenin, Tbx6 , and others.…”
Section: Cardiac Precursorsmentioning
confidence: 99%
“…10,14 The descendants of these blastomeres express Mesp, which has an essential role in the speed of migration and the specification of multipotent cardiac progenitor cells. 15 In ascidians, Mesp1/2 is regulated by beta-catenin, Tbx6, and others. Mesp1, likely representing the first element of the cardiac tool kit ( Figure 2), probably functions as a dual regulator, activating Ets1/2 and Hand-like and repressing Raldh2.…”
Section: Cardiac Precursorsmentioning
confidence: 99%
“…Basic helix-loop-helix (bHLH) transcription factors Mesp1 and Mesp2 (Saga et al 2000) under the control of T-box factor Eomes (Costello et al 2011) regulate at least part of this process in mesoderm cells by directing the expression of genes involved in cardiac specification (Hand2, Gata4, Nkx2.5, and Myocd) and cellular migration (Prickle1 and RasGRP3) while actively repressing genes regulating pluripotency (Oct4, Nanog, and Sox2) and early mesoderm (T) and endoderm (Foxa2 and Sox17) fates (Bondue et al 2008;Costello et al 2011;Chiapparo et al 2016). Although these observations suggest that Mesp1/2 genes could act as master regulators of multipotent cardiovascular specification, retrospective lineage analysis (Saga et al 2000;Yoshida et al 2008) and in vitro differentiation studies (Chan et al 2013) have shown that Mesp1-expressing cells also contribute to a wide range of noncardiac derivatives, including hematopoietic precursors, skeletal muscle cells, and head mesenchyme.…”
mentioning
confidence: 99%
“…During developmental processes and cancer progression, PRICKLE1 is required for oriented cell migration 2, 9, 11, 37 . At the molecular level, we and others have shown that PRICKLE1 contributes to localize VANGL at the plasma membrane 8, 12 , LL5β at the +ends of the microtubules 11 , and to restrict localization of the Rho-GAP at the edge of the migrating cancer cells 10 .…”
Section: Discussionmentioning
confidence: 99%